"Because we are all people": outcomes and reflections from young people's participation in the planning and design of child-friendly public spaces. Issue 12 (1st December 2016) - Derr, Victoria; Tarantini, Emily
ABSTRACT: Child-Friendly Cities were conceived as a means to integrate children's rights into city decision-making and governance. Participatory research about child-friendly cities consistently finds overarching themes across ages and regions: children desire access to services, nature, and play; freedom from physical danger; and opportunities for inclusion within the city. This article explores a two-year visioning and participatory design process that engaged approximately 225 young people, aged 4–16, in the planning and design of a prominent public space in the City of Boulder. While participatory research with children has received much attention in the academic literature, much less attention has been given to what can be achieved through sustained integration of children into municipal planning processes, particularly in the USA. This paper thus moves children's participation beyond rhetoric and into the challenging reality of planning a city with children as a valued constituent.